Black Beauty - Sewell, Anna; Sewell, Anna, 1820-1878. (Monee, IL, 2020)
"Black Beauty, published in 1877 and set in Victorian London, was Anna Sewell's only novel. Yet it has remained a classic for 140 years. Now the beloved story of Black Beauty is retold for beginning readers with full-color illustrations on every page." --From the publisher.
JBRF3 ak
Keywords: Horses -- Juvenile fiction; Great Britain -- History -- 19th century -- Juvenile fiction